Analisa Dampak Program CSR PT PLN Indonesia Power Terhadap Perubahan Sosial dan Lingkungan: Studi Kasus Mitra Binaan Kelompok Tani Cireban Jaya - Aziz, Rosihan Miftahul; Rahandini, Nikka Larasati; Hayattunnisa, Nida; Nursundanis, Nisa (Riwayat: Educational Journal of History and Humanities, 2025)
The concept of Corporate Social Responsibility (CSR) was born as a form of concern from the business world towards community development and environmental preservation. This study aims to analyze the impact of the CSR program of PT PLN IP UBP Banten 2 Labuan on social and environmental changes in the Cireban Jaya Farmers Group as a fostered partner. With a case study approach, this study describes the dynamics of the field, the challenges faced, and the contribution of the CSR program in supporting the achievement of sustainable development goals (SDGs). The study was conducted in Kaduengang Village, Cadasari District, Pandeglang Regency, within the operational area of PT PLN IP UBP Banten 2 Labuan. Data were collected through handwritten notes, drawings, photographs, and objects. Data sources consist of primary and secondary data. Primary data were obtained through interviews and direct observation of the Cireban Jaya Farmers Group and the company. Secondary data were obtained from documents from related agencies, in the form of reports and records of the CSR program. The GREEN sheep farming program showed very positive results. Members of the Cireban Jaya Farmers Group felt a real economic impact. This CSR program not only has an impact on social change, but also makes a positive contribution to the environment and community of Kaduengang Village.